Comparative study on the fish diversity from natural and bauxite post-mining in wetland system of Bintan Island, Indonesia - TRI APRIADI; GINANJAR PRATAMA; RISANDI DWIRAMA PUTRA; JUMSURIZAL JUMSURIZAL; YALES VEVA JAYA; MUHAMMAD FIRDAUS; HERU DIWAN ARPAS; ANI SURYANTI (Society for Indonesian Biodiversity, 2018)
Apriadi T, Pratama G, Putra RD, Jumsurizal, Jaya YV, Firdaus M, Arpas HD, Suryanti A. 2018. Comparative study on the fish diversity from natural and bauxite post-mining in wetland system of Bintan Island, Indonesia. Biodiversitas 19: 967-973. In this study, the fish populations between two different wetland systems in Bintan Island, Indonesia, i.e., bauxite post-mining (Kijang) and natural wetland (Toapaya) were compared and to propose a newly index namely Environomic of Fishes Index (EFI) to their respective ecosystems. The purposive random sampling at six stations, each of three stations representing bauxite mining (Kijang) and three stations representing a natural wetland (Toapaya) were used in this research. The numbers of fish species and the abundance were enumerated. The new index derived from the value of diversity index (Shannon), similarity index (Evenness), dominance index (Simpson's), conservation status, and economic value were also evaluated. The natural wetland has higher fish diversity than bauxite post-mining. The total species found were twenty-four. The same seven species were found in both areas. Twelve species were obtained from bauxite post-mining, and nineteen species were obtained from natural wetland. Puntius tetrazona and Rasbora heteromorpha were the common species in area study. The diversity and dominance index was at low category, Evenness index was at high category in all stations, except in tidal swamp station at bauxite post-mining. The EFI in natural wetland was higher than bauxite post-mining. The three community index value, economic value, and conservation status of natural wetland were higher than bauxite post-mining.